The path for innovative severe accident neutronics studies in ZPRs. Part I.1 - Analysis of SNEAK-12A experiments for core disruption in LMFBRs. (January 2017) - Margulis, M.; Blaise, P.; Gabrielli, F.; Gruel, A.; Mellier, F.; Gilad, E.
Abstract: The present work details a new benchmark to be produced to the International Community, for dealing with neutronics code validation in the frame of the analysis of severe accidents in Sodium Fast Reactors (SFRs) leading to core degradation and material relocation. The benchmark is based on analysis of selected experiments performed at the Schnelle Null-Energie-Anordnung Karlsruhe (SNEAK). The SNEAK-12A experiments have been considered where core distorted configurations have been simulated. In the paper, the experimental results have been analyzed by using TRIPOLI-4, MCNPX2.7, and Serpent-2 Monte Carlo codes as reference tools, and the ERANOS system of codes for deterministic calculations, all based on JEFF-3.1.1 nuclear data libraries. The complete material balance, and the main degradation sequences are provided within the manuscript. Preliminary results on available experimental results (keff ) are given, and additional local quantities are calculated, such as axial flux distributions, as well as detector responses as function of the distance to the degraded part. The benchmark offers an excellent opportunity to validate calculation schemes for strongly heterogeneous interfaces, in particular the preparation of homogenized self-shielded neutron cross-sections for deterministic core calculations, as well as leakage treatment in locally very heterogeneous media. This work is done within the frame of new core design capacities and new ways of conducting experiment in Zero Power Reactors, such as the ZEPHYR project led independently by CEA. The present analysis will be completed by a full nuclear data sensitivity and uncertainty analysis of the reactivity coefficients and k eff in a companion paper.